2011
DOI: 10.1293/tox.24.195
|View full text |Cite
|
Sign up to set email alerts
|

Background Data for General Toxicology Parameters in RccHanTM:WIST Rats at 8, 10, 19 and 32 Weeks of Age

Abstract: Recently, RccHanTM:WIST (Wistar Hannover) rats were introduced to toxicity studies in Japan. The present study was performed to obtain control data for general toxicological parameters as an aid for interpretation of results in toxicity studies using this strain of rats. Four test groups comprising of 25 male and 25 female RccHanTM:WIST rats were housed for 2, 4, 13 or 26 weeks from 6 weeks of age and observed and examined for clinical observation, body weight, food consumption, urinalysis, hematology, blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…During the process of nonclinical drug safety evaluation, the toxicity of some drugs may only result in animal organ weight or organ coefficient changes. Therefore, organ background data is particularly important because they not only can be used to determine whether treatment group animal organ weights are in the range of background data or not but also provide an important reference to provide to pathologists for gross anatomy and microscopic examinations 2 . In many institutes including our laboratory in China, CD(SD) (Sprague-Dawley) rats are used predominantly as experimental models in toxicity studies, and they have been used as traditional animal models for assessing carcinogenic potential of various kinds of compounds 3 .…”
Section: Introductionmentioning
confidence: 99%
“…During the process of nonclinical drug safety evaluation, the toxicity of some drugs may only result in animal organ weight or organ coefficient changes. Therefore, organ background data is particularly important because they not only can be used to determine whether treatment group animal organ weights are in the range of background data or not but also provide an important reference to provide to pathologists for gross anatomy and microscopic examinations 2 . In many institutes including our laboratory in China, CD(SD) (Sprague-Dawley) rats are used predominantly as experimental models in toxicity studies, and they have been used as traditional animal models for assessing carcinogenic potential of various kinds of compounds 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Through this work, we realized that there were high incidences of corneal mineralization in Wistar Hannover rats. A greater incidence of corneal mineralization in Wistar Hannover rats as one of the histological characteristics of this strain was reported 11 , but to our knowledge, there are no reports concerning histological details of corneal mineralization in this strain. In this study, we demonstrated the histopathological and ultrastructural characteristics of corneal mineralization in Wistar Hannover rats, as well as its incidence.…”
Section: Introductionmentioning
confidence: 70%
“…In large sample sizes, 'spontaneously' occurring outliers are expected. Collection of historical data including spontaneous incidences of outliers within laboratory specific data is routinely done in toxicology (examples: Hayakawa et al, 2013;Lee et al, 2012;Okamura et al, 2011). In addition, the incidence of outliers in clinical chemistry or hematology and unusual histopathologic findings in controls is surveyed in larger databases.…”
Section: Discussionmentioning
confidence: 99%